LEVEL OF MENTAL TOUGHNESS ON ACADEMIC ACHIEVEMENT OF STUDENT-ATHLETES UNIVERSITI TUN HUSSEIN ONN MALAYSIA (UHTM) - Samsudin, Shahifarhan; Rozali, Mohd Zulfadli; Ibrahim, Badaruddin; Hamdan, Nor Hidayah (The journal of contemporary issues in business and government, 2021)
The active involvement of student-athletes in sports and representing themselves in sports tournaments is the cause of students-athletes who further study in Higher Education Institution to get unsatisfactory results and low performance in academic achievement. Among the causal factors of this scenario is due to the mental toughness of the student athlete whom are deem to be weak which influence their learning performance. Thus, the purpose of this study is to identify the level of the mental toughness of students-athletes towards the academic achievement in Universiti Tun Hussein Onn Malaysia (UTHM). The research design used in this study is quantitative method approach. A total of 210 UTHM student-athletes were involved in the survey questionnaire. This study uses the instrument Mental Toughness Questionnaire 48 (MTQ48) that has been adapted and adopted from previous research. Data were analysed using descriptive statistical analysis to identify each element of UTHM student-athletes mental toughness level, independent T-Test statistical analysis test to determine differences in mental toughness level with the gender of UTHM student-athletes and testing using Pearson correlation statistical analysis to determine the relationship between mental toughness and the academic achievement of UTHM student-athletes. The results of the study showed that there was no significant relationship between the elements of mental toughness with the academic achievement of UTHM student-athletes. The relationship between the elements of mental toughness with the academic achievement of student-athletes was moderately strong with values r = -0.033 and sig = 0.64 (p> 0.05). The results of the study prove that the relationship between the mental toughness of students-athletes does not affect the academic achievement of UTHM student-athletes.